Pekanbaru City Snack E-Commerce Application Design Based on Android - Panji Rachmat Setiawan; Ardiansyah Ardiansyah (UIR PRESS, 2022)
E-Commerce is a concept that quite developed in the field of information technology. E-Commerce gives more convenience and advantages when compared with conventional, including all the information needed by cunsomers can be accessed more detail, without being limited with place and time, and transactions process can be done much easier. So that the implementation of this system will make it easier and more profitable for many parties, both consumers and sellers. This development method in building E-Commerce application is based on the theory of the Waterfall Model. Waterfall is a software development methodology, which proposes an approach to systematic and sequential software which starts at the system progress level throughout the analysis, design, code, testing and maintenance. The purpose of this research is to produce Pekanbaru city snack E-Commerce application based on android. By implementing this system will make it easier and more profitable for many parties, both consumers and sellers.